Faktor Risiko Kualitas Tidur Perawat di Rumah Sakit Tugu Ibu Cimanggis Kota Depok - Haris Muzakir; Anna Fitriani (Fakultas Kesehatan Masyarakat Universitas Andalas, 2023)
The need for nurses in Indonesia is still high because the need for health services in Indonesia is also increasing. The duties carried out by nurses are very vulnerable to health. Nurses will experience poor sleep quality from the tasks they do. Poor sleep quality will impact mental and health conditions because nurses have fewer hours of sleep. Lack of sleep can reduce medical and mental conditions, so the workability of nurses will decrease—Ninety-three respondents from nurses who work in Tugu Ibu hospital, Cimanggis Depok West Java. The type of research is quantitative, using a cross-sectional approach. The cross-sectional approach analyses the relationship between the independent variables, namely age, gender, shift work and body mass index, with sleep quality experienced by nurses at a private hospital in the Cimanggis area, Depok West Java. The results of the chi-square test stated that there was no significant relationship between age and sleep quality (p = 0.051). There was a significant relationship between sleep quality and gender (p = 0.050), shift work (p = 0.002) and body mass index (p = 0.002). =0.001).